2017
DOI: 10.3892/ijmm.2017.2952
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of mdx-4cv serum reveals highly elevated levels of the inflammation-induced plasma marker haptoglobin in muscular dystrophy

Abstract: Abstract. X-linked muscular dystrophy is caused by primary abnormalities in the Dmd gene and is characterized by the almost complete loss of the membrane cytoskeletal protein dystrophin, which triggers sarcolemmal instability, abnormal calcium homeostasis, increased proteolysis and impaired excitation-contraction coupling. In addition to progressive necrosis, crucial secondary pathologies are represented by myofibrosis and the invasion of immune cells in damaged muscle fibres. In order to determine whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 87 publications
6
42
0
Order By: Relevance
“…Biochemical and proteomic studies of the inflammatory pathology of dystrophic muscles have established that progressive muscle wasting is reflected by an altered rate of protein release into the circulatory system and other significant plasma fluctuations (Hathout et al 2016). Serum analysis using both conventional gel electrophoresis in combination with densitometric scanning (John and Purdom 1989) and label-free LC-MS/MS (Murphy et al 2017) revealed a significantly increased concentration of the inflammation-inducible plasma marker haptoglobin in muscular dystrophy. Since this acute phase response protein is a reliable marker of inflammation that is usually associated with tissue damage (Wang et al 2001), dystrophinopathies appear to be closely linked to sterile inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical and proteomic studies of the inflammatory pathology of dystrophic muscles have established that progressive muscle wasting is reflected by an altered rate of protein release into the circulatory system and other significant plasma fluctuations (Hathout et al 2016). Serum analysis using both conventional gel electrophoresis in combination with densitometric scanning (John and Purdom 1989) and label-free LC-MS/MS (Murphy et al 2017) revealed a significantly increased concentration of the inflammation-inducible plasma marker haptoglobin in muscular dystrophy. Since this acute phase response protein is a reliable marker of inflammation that is usually associated with tissue damage (Wang et al 2001), dystrophinopathies appear to be closely linked to sterile inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were desalted prior to analysis using C18 spin columns (Thermo Scientific) and 500ng was loaded onto an Ultimate 3000 NanoLC system (Dionex Corporation, Sunnyvale, CA, USA) coupled to a Q-Exactive mass spectrometer (Thermo Fisher Scientific). The raw data were analysed using Progenesis QI for Proteomics software (version 3.1; Non-Linear Dynamics, a Waters company, Newcastle upon Tyne, UK) as previously described, 61 with following modifications: the filter mass peaks with charge states from+1 to+6 was applied to the MS/MS data files, peptides were identified using taxonomy: Homo sapiens in the SwissProt database and peptides with XCorr scores>1.9 for +1 ions,>2.2 for +2 ions and>3.75 for +3 ions or more (from Sequest HT) were selected.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison, the CD4:CD8 ratio for the group of dogs was 1.74, consistent with our results for Golden Retriever dogs. Other animal model of muscular dystrophy presented a large number of increased versus decreased protein species in mdx-4cv serum by comparative spectrometry mass tolls (Murphy et al 2017).…”
Section: Discussionmentioning
confidence: 99%